Fractional Version of Hermite-Hadamard and Fejér Type Inequalities for a Generalized Class of Convex Functions. (22nd July 2022) - Geng, Lei; Saleem, Muhammad Shoaib; Aslam, Kiran Naseem; Bano, Rahat
Abstract : In the present paper, we deal with some fractional integral inequalities for strongly reciprocally p, h -convex functions. We established fractional version of Hermite-Hadamard and Fejér type inequalities for strongly reciprocally p, h -convex functions. Our results extend and generalize many exiting results of literate.